2020
DOI: 10.1111/cas.14343
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum soluble interleukin‐23 receptor and related T‐helper 17 cell cytokines in non‐small cell lung carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractThe signaling of interleukin (IL)-23 and its receptor (IL-23R) play a crucial role in the development of cancers. However, the clinical significance of human serum soluble IL-23R (sIL-23R) and its relationship with IL-23 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The interference of the soluble form of cytokine receptors in the cytokine-receptor axis yields the complexity of cytokine signaling and sequential inflammation, which may in turn determine cancer development and progression [ 14 , 26 ]. Numerous studies, therefore, have assessed the potentiality of soluble forms of receptors as diagnostic and survival predictors using patients’ blood samples [ 17 , 18 , 27 30 ]; in fact, serum-soluble interleukin-2 receptor has been widely utilized as an adjunct to the diagnosis and a response evaluation of malignant lymphoma in the clinical setting [ 30 ]. In the current study, the combination of sCD74 and MIF was a significant survival predictor for melanoma patients with advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…The interference of the soluble form of cytokine receptors in the cytokine-receptor axis yields the complexity of cytokine signaling and sequential inflammation, which may in turn determine cancer development and progression [ 14 , 26 ]. Numerous studies, therefore, have assessed the potentiality of soluble forms of receptors as diagnostic and survival predictors using patients’ blood samples [ 17 , 18 , 27 30 ]; in fact, serum-soluble interleukin-2 receptor has been widely utilized as an adjunct to the diagnosis and a response evaluation of malignant lymphoma in the clinical setting [ 30 ]. In the current study, the combination of sCD74 and MIF was a significant survival predictor for melanoma patients with advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…The CD4 + T cell subsets regulate tumor growth differently [ 59 ]. Th1 cells in tumors protect the host against tumor growth, whereas Th17 and Treg cells are usually associated with progression of the disease, and Th2 cells do not correlate with clinical outcomes in many cases [ 59 , 60 , 61 , 62 , 63 ]. The anti-CTLA-4 treatment upregulated the frequency of Th1, Th2, Th17, and Treg cells in TC-1/dCD80-1-induced tumors.…”
Section: Discussionmentioning
confidence: 99%
“…sIL-23R affects Th17 differentiation and stability because it causes the failure of STAT3 signaling, thus preventing excessive immune inflammation in the body and reducing Th17dependent disease damage (Raymond et al, 2015). Recently, Liu et al (Liu et al, 2020) demonstrated sIL-23/sIL-23R as a new serological marker for predicting disease progression as well as using sIL-23R (D9) to predict inflammatory diseases. In our previous work, as well as a number of studies (Larosa et al, 2019;Vukelic et al, 2020Vukelic et al, , 2019 we demonstrated an elevated IL-23 level in patients with SLE, especially those who develop lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%